2015
DOI: 10.1186/s12889-015-2406-x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the complex determinants of height and adiposity in disadvantaged daycare preschoolers in Salvador, NE Brazil through structural equation modelling

Abstract: BackgroundEarlier we reported on growth and adiposity in a cross-sectional study of disadvantaged Brazilian preschoolers. Here we extend the work on these children, using structural equation modelling (SEM) to gather information on the complex relationships between the variables influencing height and adiposity. We hope this information will help improve the design and effectiveness of future interventions for preschoolers.MethodsIn 376 preschoolers aged 3–6 years attending seven philanthropic daycares in Salv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
2
2
1
1
Order By: Relevance
“…Both Wiria et al [ 44 ] and Li et al [ 34 ] showed that adults infected with intestinal parasites were more likely to have a lower BMI ( p < 0.05). This same pattern was observed in children using various measures of weight-for-height, as reported by Gerber et al [ 30 ], Verhagen et al [ 42 ], Zhou et al [ 45 ], Geltman et al [ 29 ], Chu et al [ 28 ], Sayasone et al [ 40 ], Lander et al [ 33 ] and Zavala et al for Ascaris infection ( p < 0.05) [ 46 ]. Several other studies also showed parasitic infections associated with lower weight-for-height indicators, although the outcomes were not statistically significant (Patel and Khandekar [ 36 ], Casapia et al [ 27 ], Amare et al [ 26 ], Sanchez et al [ 39 ], Orden et al [ 35 ] and Rivero et al [ 37 ]).…”
Section: Resultssupporting
confidence: 79%
“…Both Wiria et al [ 44 ] and Li et al [ 34 ] showed that adults infected with intestinal parasites were more likely to have a lower BMI ( p < 0.05). This same pattern was observed in children using various measures of weight-for-height, as reported by Gerber et al [ 30 ], Verhagen et al [ 42 ], Zhou et al [ 45 ], Geltman et al [ 29 ], Chu et al [ 28 ], Sayasone et al [ 40 ], Lander et al [ 33 ] and Zavala et al for Ascaris infection ( p < 0.05) [ 46 ]. Several other studies also showed parasitic infections associated with lower weight-for-height indicators, although the outcomes were not statistically significant (Patel and Khandekar [ 36 ], Casapia et al [ 27 ], Amare et al [ 26 ], Sanchez et al [ 39 ], Orden et al [ 35 ] and Rivero et al [ 37 ]).…”
Section: Resultssupporting
confidence: 79%
“…Although the mean As value that we found in our study was significantly higher in those exposed to ETS, it was in the normal range according to a study by Hindmarsh et al (0.33 ± 0.11 µg/g) 39 . The mean As levels in Brazil (0.04 µg/g) and Spain (0.067 µg/g) were lower than those found in the present study (0.33 µg/g) 40 . In our study, younger age and guests smoking inside the house were found as factors that increased As levels.…”
Section: Discussioncontrasting
confidence: 62%
“…39 The mean As levels in Brazil (0.04 µg/g) and Spain (0.067 µg/g) were lower than those found in the present study (0.33 µg/g). 40 In our study, younger age and guests smoking inside the house were found as factors that increased As levels.…”
Section: 4 | Discussionsupporting
confidence: 51%
“…A t -test was used to compare the values between 2007 and 2014. Based on former works of literature, a pairwise correlation test was used to produce the correlation matrix for each of the variables known or hypothesised to influence the CVD of the adult [ 28 ]. General estimating equation (GEE) test is a development of the generalised linear model to observe the association between independent variables and dependent variables [ 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%